A mobile revolution in sub-Saharan Africa? - (:unkn) unknown (My University, 2020)
The rapid growth of mobile phones in Africa has generated widespread enthusiasm. This is evidenced by the reports and programmes of development aid institutions and by the recent creation of a “community” bringing together researchers, NGOs, donors and companies around new technologies for development (Information and Communication Technologies for Development or ICTD). In the first article of this issue of Réseaux devoted to recent research on the use of mobile technologies in sub-Saharan Africa, we review the situation. Has the mobile kept its promises? What do we know about its actual uses in sub-Saharan Africa? The article reports on a significant gap between the promises of international programmes or economic forecasts, and the reality of practices and usage. It presents the articles in the special issue, which highlight the importance of mobile phones in the daily lives of populations, as well as the plurality and complexity of the actual take up of this technology and its significance for the continent.
Keywords: African Research